The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1046/j.1523-1747.1998.00328.x
|View full text |Cite
|
Sign up to set email alerts
|

Erythema Multiforme Associated Human Autoantibodies Against Desmoplakin I and II: Biochemical Characterization and Passive Transfer Studies Into Newborn Mice

Abstract: The demonstration of circulating autoantibodies directed against the constitutive desmosomal plaque proteins desmoplakin (dp) I and II in mucocutaneous lesions in a subset of patients with erythema multiforme major, suggests that humoral immune mechanisms may play a role in the pathogenesis of this severe skin disease. In this study we identified a specific peptide sequence--YSYSYS--representing an antigenic binding site for the human autoantibodies. This epitope is localized at the extreme carboxy terminal do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 39 publications
1
45
0
Order By: Relevance
“…In fact, several reports demonstrate penetration of IgG autoantibody into living cells (19,20). Notably in keratinocytes, by using passive transfer and in vitro cell culture systems, a series of recent investigations have also demonstrated that IgG autoantibodies to desmoplakin I/II, entirely intracellular desmosomal antigens, can get into living cells and reach the target antigens (21)(22)(23). Moreover, anti-nuclear IgG antibodies from patients with systemic lupus erythematosus have been shown to penetrate into living epithelial cells via receptor-mediated endocytosis and subsequently localize to the corresponding intracellular target antigens (24).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several reports demonstrate penetration of IgG autoantibody into living cells (19,20). Notably in keratinocytes, by using passive transfer and in vitro cell culture systems, a series of recent investigations have also demonstrated that IgG autoantibodies to desmoplakin I/II, entirely intracellular desmosomal antigens, can get into living cells and reach the target antigens (21)(22)(23). Moreover, anti-nuclear IgG antibodies from patients with systemic lupus erythematosus have been shown to penetrate into living epithelial cells via receptor-mediated endocytosis and subsequently localize to the corresponding intracellular target antigens (24).…”
Section: Discussionmentioning
confidence: 99%
“…Generation of anti-FcRn Ab An affinity-purified peptide-specific Ab to FcRn a2-extracellular domain was generated according to the methods as described in detail earlier (Foedinger et al, 1998). The 14 amino acids sequence peptide LNGEEFMNFDLKQG out of the a2-extracellular domain of human FcRn was used as antigen to raise a peptide-specific rabbit anti-FcRn Ab (by Charles River, Kisslegg, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Anti-plakin auto-antibodies are found in some patients. 1 EM must be distinguished from Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN), which are drug induced in most cases. [2][3][4][5] However, mucous membrane (MM) lesions of EM major (EMM) are clinically similar to those of SJS/TEN and literature remains confusing between both diseases.…”
Section: Editormentioning
confidence: 99%
“…We identified that the loss of inositol polyphosphate-5-phosphatase (INPP5A) may play a role in the development and progression of cutaneous squamous cell carcinoma (SCC). 1 Loss of INPP5A has been previously linked to cancer development and progression. 2 Inositol signalling pathways are involved in intracellular calcium release, membrane trafficking, chemotaxis, ion channel activity and many other nuclear functions.…”
Section: Editormentioning
confidence: 99%